Time and Migration : How Long-Term Taiwanese Migrants Negotiate Later Life - Sun, Ken Chih-Yan (Book collections on Project MUSE., 2021)
"Based on 115 interviews with elderly Taiwanese immigrants who have resided in the US from 30 to 50 years, Ken Sun asks in Time and Migration how the interplay between migration and time shapes the ways aging migrant populations reassess and reconstruct relationships with their children, spouses, grandchildren, community members, and home as well as host societies."--